Gender differences in the prevalence and treatment of coronary chronic total occlusions. Issue 6 (25th November 2015) - Wolff, Rafael; Fefer, Paul; Knudtson, Merril L.; Cheema, Asim N.; Galbraith, P. Diane; Sparkes, John D.; Wright, Graham A.; Wijeysundera, Harindra C.; Strauss, Bradley H.
Abstract : Background: Gender differences exist in the presentation and outcomes of patients with coronary artery disease (CAD). Our study objective was to compare gender differences in prevalence, co‐morbidities, and revascularization treatment in CAD patients with chronic total occlusions (CTOs). Methods: A retrospective analysis using the Canadian Multicenter CTO Registry, which included 1, 690 consecutive CTO patients identified at coronary angiography and a control group of 7, 682 non‐CTO patients. Results: The prevalence of women in the CTO group was significantly lower compared to the control group (19% vs. 30%, P < 0.001). Within the overall CTO group, women were significantly older than men (70 ± 12 vs. 66 ± 11 years, P < 0.001) with more comorbidities, including hypertension and heart failure. Rates of PCI in the CTO group were similar between gender (10%), however, women with CTO were treated significantly less by CABG compared to men (19% vs. 27%, P = 0.003). Moreover, compared to male patients, significantly fewer women undergoing CABG had revascularization of the CTO artery (84% vs. 93%, P = 0.03). Multivariable analysis indicated that female gender (along with age, chronic renal failure, prior MI and cerebro‐vascular disease) were independent predictors for not receiving CABG treatment for CTO. Conclusions: Female gender differences exist in CTO patients with both lower prevalence of CTOs at angiography and lower revascularization rates of CTOs by CABG. © 2015 Wiley Periodicals, Inc.